Communication Interventions to Improve Goal-Concordant Care of Seriously Ill Patients: An Integrative Review. Issue 1 (February 2020) - Bennett, Frank; O'Conner-Von, Susan
Abstract : Effective communication between clinicians and seriously ill patients and their families about a patient's goals of care is essential to patient-centered, goal-concordant, end-of-life care. Effective goals-of-care communication between clinicians and patients is associated with improved patient and family outcomes, increased clinician satisfaction, and decreased health care costs. Unfortunately, clinicians often face barriers in goals-of-care communication and collaboration, including a lack of education, time constraints, and no standardized protocols. Without clear goals-of-care communication, patients may not be able to provide guidance to clinicians about their end-of-life preferences. The purpose of this integrative review was to examine the efficacy of goals-of-care communication interventions between patients, families, and clinicians in randomized controlled trials published between 2009 and 2018. Twenty-three studies met the inclusion criteria with an overall sample (N = 6376) of patients, family members, and clinicians. Results revealed of the 6 different intervention modes, patient decision aids and patient-clinician communication consistently increased comprehension and communication. Twelve of the studies had nurses facilitate or support the communication intervention. Because nurses are a critical, trusted nexus for communication about end-of-life care, focusing on nurse interventions may significantly improve clinical outcomes and the patient experience. Abstract : Supplemental digital content is available in the text.